Turbine Type Rotary Wave Energy Converter Performance - Karakose, Perihan; Koca, Ahmet (Gazi Univ, 2024)
In this investigation, the utilization of water waves as the fluid medium is explored in the context of turbines, which are mechanical devices that convert fluid motion into rotational motion. The Volume of Fluid (VOF) model in Ansys Fluent is employed to generate regular waves and analyze the turbine's movement in a wave tank. Essential parameters such as force, pressure, momentum, and speed of the turbine are investigated to harvest electrical energy from wave energy. The study aimed to understand how these parameters changed with varying wave characteristics. Results showed that dynamic pressure and moment increase as the wavelength increased. However, the turbine's rotation speed decrease as wavelength increased. The force acting on the blades do not change significantly with wavelength but caused a time delay. The highest force applied to the turbine blades is observed at a wave height of 2 m, reaching 8000 N. Finally, the maximum turbine speed is attained at a wave height of 2 m and wave period of 7 s, reaching 87 mm/s. However, the maximum efficiency of 19.18% is achieved at a wave height of 1m and a wave period of 8.75 seconds. Because as the wave height increases, the power of the wave increases significantly, but the absorption of this power increases at a lower rate. Therefore, this study highlights the need to increase the number of wave energy conversion systems that can operate efficiently for wave forms with high wave heights.
Keywords: Wave energy; Dynamic mesh; VoF method; Rotating turbine